Improving the Performance Skills of Rubob (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article explores the methodologies and techniques for improving the performance skills of the Rubob, a traditional musical instrument prominent in Central Asian music. Through historical analysis, technical studies, and pedagogical approaches, we aim to provide a comprehensive guide for musicians and educators to enhance their proficiency and teaching methods. The study also highlights the importance of preserving the cultural heritage associated with the Rubob while integrating contemporary music education techniques.